Decreased Copper in Alzheimer's Disease Brain Is Predominantly in the Soluble Extractable Fraction. (21st October 2013) - Rembach, Alan; Hare, Dominic J.; Lind, Monica; Fowler, Christopher J.; Cherny, Robert A.; McLean, Catriona; Bush, Ashley I.; Masters, Colin L.; Roberts, Blaine R.
Abstract : Alzheimer's disease (AD) is the leading cause of dementia and represents a significant burden on the global economy and society. The role of transition metals, in particular copper (Cu), in AD has become of significant interest due to the dyshomeostasis of these essential elements, which can impart profound effects on cell viability and neuronal function. We tested the hypothesis that there is a systemic perturbation in Cu compartmentalization in AD, within the brain as well as in the periphery, specifically within erythrocytes. Our results showed that the previously reported decrease in Cu within the human frontal cortex was confined to the soluble (P < 0.05 ) and total homogenate (P < 0.05 ) fractions. No differences were observed in Cu concentration in erythrocytes. Our data indicate that there is a brain specific alteration in Cu levels in AD localized to the soluble extracted material, which is not reflected in erythrocytes. Further studies using metalloproteomics approaches will be able to elucidate the metabolic mechanism(s) that results in the decreased brain Cu levels during the progression of AD.